PENDIDIKAN ISLAM DI ERA GLOBALISASI DALAM MEMBANGUN KARAKTER BANGSA - Aziza Meria (AT-TA'LIM, 2012)
The vision and mission of Islamic education is rahmatan lil ‘alamiin, that makes Islamic education as guidance to direct the human being becomes chaliph in the world. The aim of government decre on national education system 2003 is to filterize the negative impacts of globalization which will lose national identity. The possible solution to overcome this negative effect is the teacher as well as educator should become a good model for students, discuss good topic, supervise the students continually, conduct regular supervision, and provide balance between reward and punishment.